Gender-Based Analysis of Creative Thinking Skills in Grade X Students on Work, Energy, and Alternative Energy (WE-ALT) Concepts - Atmaja, Devi Yulianty Surya; Samsudin, Achmad; Saepuzaman, Duden (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to examine the level of creative thinking skills and the distribution of its aspects based on gender and material. The study is motivated by the critical role of creative thinking in addressing the global challenges of the 21st century, particularly in relation to alternative energy as a sustainable solution. The research employs a quantitative descriptive method. Creative thinking in this study is conceptualized based on Torrance’s framework, which includes four main aspects: fluency, flexibility, originality, and elaboration. The study involved 72 Grade X students from Sumedang Regency, who completed an essay test consisting of six questions covering Work, Energy, and Alternative Energy (WE-ALT) topics. The test instrument, adopted from previous research, was empirically validated and confirmed to be reliable based on item statistics, including misfit order and reliability analysis results, ensuring its suitability for this study. Data were processed and analyzed using Microsoft Excel and the Rasch Model with Winstep version 4.7.0.0 to map students' abilities. The results show that students scored highest on the Work material, with an average score of 64, followed by the Energy material with a moderate score of 58, and the lowest score on Alternative Energy material with 36. Overall, Alternative Energy was the topic with the lowest average score for creative thinking skills, and female students outperformed male students, particularly in the fluency aspect. These findings suggest that innovative, technology-integrated, and interactive learning strategies are needed to enhance students' creative thinking skills.